The Influence of Promotions, Online Customer Reviews, and Online Customer Ratings on Decisions to Purchase Muslim Clothing Products in E-Commerce Shopee on IKHAC Students - Anggraeni, Yuniar Nanda; A’yuni, Diah Syifaul (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
Research conducted by the Global Overview Report shows that Indonesia is ranked fifth as a country with people who often shop online with a percentage reaching 36%. This research aims to measure the influence of promotions, online customer reviews, and online customer ratings on purchasing decisions for Muslim clothing products on Shopee e-commerce. This research uses quantitative methods with survey methods. A total of 100 respondents were selected using a probability sampling technique using the Slovin formula from all undergraduate students at the Institut Pesantren KH. Abdul Chalim (IKHAC). The results of this research, the T-test show that the independent variable is promotion, Online customer reviews, and online customer ratings partially have a positive and significant effect on purchasing decisions for Muslim clothing products on e-commerce Shopee among IKHAC students. In the F test, the independent variables promotion, online customer review, and online customer rating simultaneously have a positive and significant influence on the decision to purchase Muslim clothing products on e-commerce Shopee among IKHAC students. Based on the coefficient of determination value, it shows that 66.4% is influenced by the three factors above.